Learning Video with Sign Language to Improve Reproductive Health Awareness for Deaf Adolescents - Wibowo, Sarwo Edy; Anggrellanggi, Arsy; Kumalasari, Erma; Subagya, Subagya (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2023)
The purpose of this study was to determine the effectiveness of learning video media in sign language to determine the increase in reproductive health awareness for deaf adolescents. This type of research is experimental research, using One-Group Pretest Posttest Design. The subjects in this study were deaf adolescents with a targeted sample technique. Data collection with objective tests in the form of multiple choices. The validity test of the instrument used content validity with the calculation of Aiken's V, and the reliability test of the instrument used the consistency assessment technique of the raters. Data analysis using the Wilcoxon Sign Rank Test obtained the results of Zcount: -2.371 with Asymp. Sig. (2-tailed): 0.018 or p: 0.018 smaller than α: 0.05. As a result, Ho is rejected and Ha is accepted. So it is known that learning video media in sign language is effective in increasing awareness of deaf adolescents regarding reproductive health.